The Effect of Nutrition Counseling with Animation Media about Obesity on Knowledge and Habits of Fast Food Consumption in Class VIII Obese Adolescents at SMP Negeri 1 Lubuk Pakam - Windi Noveria Saragih; Abdul Hairuddin Angkat (PT FORMOSA CENDEKIA GLOBAL, 2023)
Obesity is a condition where a person has a body weight that is heavier than their ideal body weight. Excessive consumption of fast food can lead to obesity. Counseling using animated video media can increase knowledge about the importance of overcoming obesity. The aim of the research was to determine the effect of nutritional education using animation media on knowledge and fast food consumption habits and the incidence of obesity in adolescents. This research was conducted at SMP Negeri 1 Lubuk Pakam. The research period was carried out from July 2022 to June 2023 with quantitative methods using a Group Pre and Post Test design. Intervention in the form of counseling using animation media was given 3 times. The population in this study was class VIII, 319 students. The sample in this study was 32 obese students who met the criteria for being a sample. Data collection uses a questionnaire using a statistical test, namely the T-dependent test. The research results showed that the average knowledge of teenagers about obesity before counseling was 10.09, after being given counseling was 13.25. The average score for fast food consumption habits before being given counseling was 95.75, after being given counseling it was 88.09. The conclusion is that there was an influence of nutritional education using animation media on knowledge and fast food consumption habits with a value of p= 0.000. The school's suggestion is to encourage students to reduce consumption of fast food.